2022
DOI: 10.3389/fpls.2022.826007
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Coat Protein Complexes for Vesicle Formation in Plant Post-Golgi Trafficking

Abstract: Endomembrane trafficking is an evolutionarily conserved process for all eukaryotic organisms. It is a fundamental and essential process for the transportation of proteins, lipids, or cellular metabolites. The aforementioned cellular components are sorted across multiple membrane-bounded organelles. In plant cells, the endomembrane mainly consists of the nuclear envelope, endoplasmic reticulum (ER), Golgi apparatus, trans-Golgi network or early endosome (TGN/EE), prevacuolar compartments or multivesicular bodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 77 publications
0
19
0
Order By: Relevance
“…A key question emerging from this observation is whether the Y motif in OuMV MP is a functional internalization motif. Y motifs are recognized by msubunits of APs 1-4 (24,63,64). In plants, clathrin-mediated endocytosis (CME) of plasma membrane proteins is achieved by the recognition of Y motifs in their cytoplasmic domains by AP2M (56-59), and it has been previously shown that CaMV MP is able to bind Arabidopsis AP2M through three Y motifs (16).…”
Section: Discussionmentioning
confidence: 99%
“…A key question emerging from this observation is whether the Y motif in OuMV MP is a functional internalization motif. Y motifs are recognized by msubunits of APs 1-4 (24,63,64). In plants, clathrin-mediated endocytosis (CME) of plasma membrane proteins is achieved by the recognition of Y motifs in their cytoplasmic domains by AP2M (56-59), and it has been previously shown that CaMV MP is able to bind Arabidopsis AP2M through three Y motifs (16).…”
Section: Discussionmentioning
confidence: 99%
“…AP complexes typically consist of two large subunits (β and α/γ/δ/ε/ζ), a medium subunit (μ), and a small subunit (σ). They sort membrane-bound or transmembrane cargo proteins by recognizing and binding to sorting motifs or signals, such as the tyrosine motif, dileucine motif, and ubiquitin, which are present in the cytoplasmic domains of cargo proteins ( Arora and Van Damme, 2021 ; Law et al, 2022 ). Various AP complexes interact with clathrin to form clathrin-coated vesicles.…”
Section: Coat Proteins At the Tgnmentioning
confidence: 99%
“…First, Arf/Sar GTPases activated by their guanine-nucleotide exchange factor (GEF) promote the recruitment of coat proteins on the donor membrane. Coat proteins play important roles in cargo protein recognition and membrane distortion ( Singh and Jürgens, 2018 ; Arora and Van Damme, 2021 ; Law et al, 2022 ). RAB GTPases are involved in various trafficking events, such as tethering ( Saito and Ueda, 2009 ; Minamino and Ueda, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…During CCVs formation, Arf GTPases recruit adaptor protein (AP) complex, which serve as an intermediate between clathrin coat components and cargo receptors. Clathrin triskelions are recruited by AP complexes and assembled to form clathrin-coated vesicles, which are pinched from the donor membrane with the aid of the polymerizing GTPase dynamins ( Jin et al, 2001 ; Backues et al, 2010 ; Law et al, 2022 ). AP1-4 in plants have been found to be heterotetrametric complexes, comprising two large subunits (α/γ/δ/ε and β), one medium subunit (μ) and one small subunit (σ).…”
Section: Post-golgi Traffickingmentioning
confidence: 99%
“…AP1-4 in plants have been found to be heterotetrametric complexes, comprising two large subunits (α/γ/δ/ε and β), one medium subunit (μ) and one small subunit (σ). In Arabidopsis, several studies show that AP1, AP3, and AP4 participate in anterograde transport from the TGN to the vacuole/PM ( Niihama et al, 2009 ; Park et al, 2013 ; Robinson and Pimpl, 2014 ; Fuji et al, 2016 ; Hatsugai et al, 2018 ; Law et al, 2022 ).…”
Section: Post-golgi Traffickingmentioning
confidence: 99%